Rozwiąż równania:
a) 3 + 2 ( x - 4 ) = 1
b) 4 - 2 ( y + 1 ) = -2
c) 12 + 3 (2 - x ) = 0
d) 5 - 2 ( 2 - z ) = 3
e) 4 ( 2x - 1 ) + 2 ( 5 - 3x) = 0
f) 7 ( 3y + 1 ) - 6 ( 2y + 3 ) = -2
g) -5 ( 2 + 3z ) + 4 ( 4z - 3) = 1
h) -2 ( x - 3 ) - 3 ( 3x + 5 ) = 2

z góry dziękuję. :P

2

Odpowiedzi

  • Użytkownik Zadane
2010-02-04T17:57:48+01:00
A) 3 + 2 ( x - 4 ) = 1
3+ 2x- 8= 1
2x-5 =1 /+5
2x =6 /:2
x=3
b) 4 - 2 ( y + 1 ) = -2
4-2y- 2 =-2
-2-2y =-2 /+2
-2y =0
y= 0
c) 12 + 3 (2 - x ) = 0
12+ 6- 3x=0
18 -3x= 0 / -18
-3x= -18 / :(-3)
x= 6
d) 5 - 2 ( 2 - z ) = 3
5- 4 +2z =3
1+ 2z= 3 /-1
2 z = 2 /:2
z= 1
e) 4 ( 2x - 1 ) + 2 ( 5 - 3x) = 0
8x -4+ 10-6x =0
2x+ 6=0 /-6
2x= -6 /:2
x= -3
f) 7 ( 3y + 1 ) - 6 ( 2y + 3 ) = -2
21y +7- 12y- 18 =-2
9y- 11= -2 /+11
9y = 9 /:9
y=1
g) -5 ( 2 + 3z ) + 4 ( 4z - 3) = 1
-10 -15z +16z -12 =1
-22+ z =1 /+22
z= 23
h) -2 ( x - 3 ) - 3 ( 3x + 5 ) = 2
-2x+ 6-9x -15= 2
-11x -9=2 /+9
-11x = 11/ :(-11)
x= -1
Najlepsza Odpowiedź!
2010-02-04T17:59:46+01:00
A) 3 + 2 ( x - 4 ) = 1
3 + 2x -8 = 1
2x - 5 = 1
2x = 1 + 5
2x = 6 /:2 (dzielenie obustronne)
x = 3

b) 4 - 2 ( y + 1 ) = -2
4 -2y -2 = -2
-2y + 2 = -2
-2y = -2-2
-2y = -4 /: (-2)
y = 2

c) 12 + 3 (2 - x ) = 0
12 + 6 -3x = 0
-3x + 18 = 0
-3x = -18 /: (-3)
x = 6

d) 5 - 2 ( 2 - z ) = 3
5 -4 + 2z = 3
2z + 1 = 3
2z = 3-1
2z = 2 /:2
z = 1

e) 4 ( 2x - 1 ) + 2 ( 5 - 3x) = 0
8x -4 +10 -6x =0
2x + 6 = 0
2x = -6 /:2
x = -3

f) 7 ( 3y + 1 ) - 6 ( 2y + 3 ) = -2
21y + 7 -12y -18 = -2
9y - 11 = -2
9y = -2 + 11
9y=9 /:9
y = 1

g) -5 ( 2 + 3z ) + 4 ( 4z - 3) = 1
-10 -15z +16z -12 = 1
z - 22 = 1
z = 1 + 22
z = 23

h) -2 ( x - 3 ) - 3 ( 3x + 5 ) = 2
-2x +6 -9x -15 = 2
-11x - 9 = 2
-11x = 2+9
-11x=11 /:(-11)
x = -1
1 5 1